Annual Plan 2004-05 Orissa Volume-I - Planning Commission (Planning Commission, 2004)
The State of Orissa, known as the great Kalinga empire in the ancient and mediaeval times, had reached the pinnacle of glory and prosperity. It was famous for its military might, flourishing maritime trade and commerce and above all magnificent temples depicting its superb art and sculpture. But due to various reasons, historical and others that Orissa is presently one of the poorest Stales of the country in the post-independence era despite being endowed with rich human and natural resources.
Government of Orissa, Planning and Coordination Department